Super-refractory status epilepticus (SRSE): A case series of 22 pediatric patients. (March 2022) - Caputo, Davide; Santarone, Marta Elena; Serino, Domenico; Pietrafusa, Nicola; Vigevano, Federico; Fusco, Lucia
Abstract: Background: Super-refractory Status Epilepticus (SRSE) is a rare condition in which SE persists or recurs ≥24 h after the onset of anesthesia. Although its characteristics are well defined in adulthood, only few studies on children are available. Methods: we retrospectively analyzed the population of patients with SRSE aged <18 years treated in the Pediatric Intensive Care Unit of the Bambino Gesù Pediatric Hospital. We assessed clinical history, etiology, neuroimaging, electro-clinical features of SRSE, treatments and neurological status after SRSE cessation. Results: We identified 22 children with median age at SRSE onset of 3.1 years (IQR 1.3–7.3) and SRSE duration of 22.0 days (IQR 11.2–30.5) Before SRSE, 17 patients (77.3%) had an abnormal neurological examination, 18 (81.8%) had a diagnosis of epilepsy, 8 of which already presented an episode of SE. Only 4 patients (18.2%) had New Onset SRSE. Eleven patients had a progressive etiology (PE), 9 had a remote etiology (RE) and 2 patients had an acute etiology (AE). Amongst PE the most frequent etiologies were mitochondrial diseases, while among RE they were Developmental Epileptic Encephalopathies of genetic origin. Time to SRSE cessation was significantly longer in PE (p = 0.04). After SRSE, 8 patients, (7 with PE) showed a significant worsening of neurological status. In this group, mean time at SE cessation was significantly longer (p = 0.05). Conclusions: pediatric SRSE is mostly associated with progressive diseases and remote etiologies. Underlying etiology seems to impact both on SRSE duration and subsequent neurological evolution, however more studies are needed to confirm these findings. Highlights: SRSE often occurs in children with a history of epilepsy and neurological disorders. It is caused more frequently by progressive and remote etiologies. Progressive etiologies show longer duration of SRSE and a worse neurological outcome.